(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
The Siddha system of medicine is one of the six recognized systems in the Indian system of medicine. The medicines comprise herbals, minerals, metals, and animal origins. Thurusu (Copper Sulphate) is a naturally occurring inorganic compound, but it can be prepared synthetically as per the procedures present in the Siddha literature as Vaippu muraigal. It is used in Siddha medicine as a single drug or in combination drugs after the detoxification process, which is termed as “Suthimurai” particularly incorporated for Schedule E drugs, which are listed in the Drugs and Cosmetics Act of 1940. Therapeutically, administered in the form of Parpam, Chenduram and externally applied to cure even chronic wounds. In this study, thurusu prepared as per Vaippu murai to assess the concentration of heavy metals present in the drug. The preparations are based upon the Siddha literature “Bogarsarakkuvaippu-800”. The heavy metals present in the Thurusu vaippu were analysed and the results showed the presence of heavy metals below the detection limit, but copper (350.125mg/l) and sulphur (471.204 mg/l) are present above the limit of the pharmacopoeial laboratory for Indian medicine (PLIM) guideline. Further processing of Suthimuraigal determines the concentration level of Thurusu vaippu for therapeutic purposes. Further research on Thurusu vaippu which paved the way to standardize the Thurusu vaippu muraigal.